Science, Art and Nature in Medieval and Modern Thought. - Crombie, A. C. (Continuum International Pub. Group, 1990)
The author sees the history of Western science as the history of a vision and an argument, initiated by the ancient Greeks in their search for principles at once of nature and of argument itself. This volume explores science, art and nature in medieval and modern thought.